2021
DOI: 10.1177/09544054211056420
|View full text |Cite
|
Sign up to set email alerts
|

Lubricating effect of graphene during ultra-precision mechanical polishing by atomic scale simulation

Abstract: As a new two-dimensional material with unique friction and wear properties, graphene often serves as a solid lubricant. In order to better understand the lubrication effect of graphene in the process of three-body polishing of single crystal silicon with diamond abrasive, a molecular dynamics model of this process was established in this study. Further, the changes of coordination number, friction coefficient, temperature, potential energy, stress, and surface/subsurface damage in the process of three-body pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…As far as abrasive material is concerned, diamond comes in top list due to it hardness, thermal conductivity, sharpness, etc. In order to understand the effect of diamond abrasive for polishing, a three-body mechanism of polishing on silicon with diamond abrasive was investigated using a molecular dynamics simulation [13]. In this study, graphene lubrication enhances the heat dissipation and helps to reduce surface defects and subsurface damage Mechanical polishing on stainless steel with diamond abrasive was investigated through molecular dynamics simulation, and it is observed that the finishing force and velocity damage the diamond abrasive by altering its phase from diamond cubic to graphite [14].…”
Section: Introductionmentioning
confidence: 99%
“…As far as abrasive material is concerned, diamond comes in top list due to it hardness, thermal conductivity, sharpness, etc. In order to understand the effect of diamond abrasive for polishing, a three-body mechanism of polishing on silicon with diamond abrasive was investigated using a molecular dynamics simulation [13]. In this study, graphene lubrication enhances the heat dissipation and helps to reduce surface defects and subsurface damage Mechanical polishing on stainless steel with diamond abrasive was investigated through molecular dynamics simulation, and it is observed that the finishing force and velocity damage the diamond abrasive by altering its phase from diamond cubic to graphite [14].…”
Section: Introductionmentioning
confidence: 99%